Kesejahteraan psikologi, kesejahteraan spiritual dan efikasi kendiri dalam kalangan kaunselor organisasi di Kementerian Pendidikan Malaysia / Mahani Ismail - Mahani , Ismail (2019)
This study aims to determine the level of psychological well-being, spiritual well being and self-efficacy among organizational counselors in the Ministry of Education Malaysia. besides, the study also aims to determine a priori model that involved the relationship between the spiritual well-being, self efficacy and psychological wellbeing with the survey data, verify the spiritual well-being as a mediator in the model, and examine the indirect effects of spiritual well-being on psychological well-being in the model. Finally, the study will also determine whether gender, location of the workplace, and working experience serves as a moderator in the study. Does gender play a role as a moderator in the propose model 'moderated - mediation' was also examined. Quantitative method using a survey was used to gather the data. A total of 203 counselors who work in the District Education Office, the State Education Department, Matriculation College, the Institute of Teacher Education and also in Psychology and Counseling Division Ministry of Education were selected as respondents. The instruments used in this study is Ryff Psychological Well-being Scale(1989), Spiritual Well being Scale(1982) and Counselor Self -Efficacy Scale (1996). Data was analyzed using the Statistical Package for Social Science version 20 (SPSS) and software Analysis of Moment structure version 21 (AMOS). Descriptive analysis was also used to measure the mean, standard deviation, frequency and percentage. Moreover construct factor analysis (CFA) and structural equation modeling (SEM) was also performed in this study. The results showed that the level of psychological well being and self-efficacy of organization counselor is high. While the level of self-efficacy is moderate . This study also showed that a significant fit model for counselors’ psychological well being with the research data. Test of goodness fit model was assessed through multiple indices that are Root Mean Square Error of Approximation (RMSEA), Comparative Fit Index (CFI) and Chi Square / Degree of Freedom (Chisq / Df) to achieve a fit model. The value of fit for structural model of psychological well-being proved to be fit and accepted (GFI = .92, CFI = .92, RMSEA = .09). Sobel test analysis statistics show that the spiritual well being model serve as a mediator in this study (3.18, p <0.05 sig). The study found that there is an indirect effect of the spiritual well-being on the psychological well-being in the study. Spiritual well-being act as a partial mediator in the relationship between self-efficacy and psychological well-being. The results also showed gender, location of the workplace and working experience serve as a moderator in the model of moderated – mediation with a significant value in mediation (M = .147, F = .130) and without mediation (M= -.406, F= -.432). The results of this study provide a foundation to form a good counselors psychological well-being model with an additional emphasis on the spiritual aspects in addition to the existing psychological aspects. Implication of the study to future researchers and counseling practitioners are discussed.